The influence of maternal long term health conditions including multimorbidity on child oral health: A scoping review and evidence gap map protocol [version 2; peer review: 2 approved, 1 approved with reservations, 1 not approved] - Scott McGregor; Faith Campbell; Ryan Stewart; Louise Marryat; Heather Cassie; Jan Clarkson (Wellcome Open Research, 2024)
Objective This scoping review will map the extent and type of evidence in relation to the association between maternal long term health conditions (LTCs), including multimorbidity, and child oral health. Introduction Newer theories are emerging that detail the many factors that can influence child oral health at child, family and community levels. More recently, the association between maternal general health and child oral health has been explored, with preliminary evidence suggesting a link between shared environmental factors and diet/substance use during pregnancy causing childhood caries. Inclusion criteria All published studies that describe the relationship between maternal LTCs (including multimorbidity) and child oral health. There will be no limitation on the date of publication due to the limited number of studies available from the initial search of PubMed. The review will exclude case studies, abstracts, and grey literature. Literature must be in English language. Methods The following databases will be searched; CINAHL, Cochrane Library, Maternity and Infant Care, Medline via PubMed, Scopus, Web of Science. The search will include sources in English only and will be undertaken between April and July 2024. Studies to be included will be of any type of study design that describe a relationship between maternal long term health conditions, including maternal long term oral health conditions, and child oral health. Data extraction will be undertaken using tabulation of results by at least two independent reviewers. Narrative analysis of the evidence will be undertaken, and results will be presented in a narrative and tabular manner due to the heterogenous and limited evidence base found in the test search. This review has been registered prospectively on Open Science Framework, (https://doi.org/10.17605/OSF.IO/ECSWJ). The review will also inform an Evidence Gap Map (EGM) to illustrate the current evidence base regarding maternal health factors that influence child oral health.